PENGARUH MODEL BALANCED LITERACY TERHADAP HASIL BELAJAR BAHASA INDONESIA PESERTA DIDIK KELAS III SDN SIDOKLUMPUK SIDOARJO - Inayatul Izah; Muhammad Assegaf Baalwi; Achmad Wahyudi (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
This research was conducted at SDN Sidoklumpuk Sidoarjo. The purpose of this study was to determine the effect of the Balanced Literacy model on Indonesian language learning outcomes for third-grade students at SDN Sidoklumpuk Sidoarjo. This research includes quantitative research where the data generated is in the form of numbers. The research data were calculated using SPSS software version 16. This type of research is quasi-experimental research (quasi-experimental) with a Nonequivalent Control Group Design. Data collection techniques used in this study were interviews and tests. The data analysis technique used a validity test, reliability test, normality test, homogeneity test, and different test t-tests (independent sample test). The results of the study stated that from the results of testing the research hypothesis, there was an effect of the Balanced Literacy Model on Indonesian language learning outcomes in third-grade students at SDN Sidoklumpuk Sidoarjo. This is evidenced by the value on the different t-tests (independent sample test) which shows that sig 0.006 0.05 then Ho is rejected or Ha is accepted. So it can be concluded that the hypothesis Ha states there is an effect of the Balanced Literacy Model on the learning outcomes of Indonesian class III students